Ventilatory muscle strength in cystic fibrosis patients: a literature review - J.P. Heinzmann-Filho; P.J.C. Marostica; M.V.F. Donadio (Monaldi Archives for Chest Disease, 2015)
The ventilatory mechanic changes that occur in cystic fibrosis (CF) patients may lead to alterations in the respiratory muscle strength levels. However, the findings regarding the strength profile in these patients are still contradictory. Objective: To evaluate, trough a literature review, the respiratory muscle strength behavior in CF patients. We have performed a search in Medline/Pubmed, Scielo, IBECS and LILACS databases selecting observational cross-sectional, prospective or retrospective studies, as well as randomized clinical trials, published between 1981 and 2011, using the following terms: cystic fibrosis, respiratory muscle strength, inspiratory maximal pressure and muscle training. The majority of the studies 71,24% have shown normal or above normal respiratory muscle strength, whilst 28,57% demonstrated reduced or near-normal values. Most of these findings were attributed to an increased work of breathing as a result of airway obstruction and chronic persistent cough. Taken together, the analyses of selected studies have showed conflicting findings regarding respiratory muscle strength behavior in these patients. However, most of the studies seem to indicate that CF patients presented maximum respiratory pressures normal or above predicted values.